HIGH DENSITY JUVENILE SHRIMP (Penaeus monodon) PRODUCTION WITH DIFFERENT DURATIONS OF REARING IN ACID SULFATE SOIL-AFFECTED POND - Akhmad Mustafa; Jesmond Sammut (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
An experiment was conducted to evaluate the effectiveness of producing juvenile shrimp in a reservoir pond constructed in acid sulphate soils (ASS). Many ponds constructed in ASS pose a significant economic risk due to high mortality and poor growth. In Indonesia, abandonment of ponds in ASS is widespread and alternative farming practices, such as production of juvenile shrimp, offer farms opportunities to lower their production risks. The experiment involved rearing juvenile shrimp at a high stocking density (3,000 individuals/m2) using hapas in a formerly unproductive pond located in Luwu Regency, South Sulawesi, Indonesia. The treatments tested included rearing periods of three and six weeks with four replications. A survival of 83.62% was achieved after rearing for three weeks compared to 45.44% after six weeks. Although there was a sixfold increase in the mean weight of shrimp from three to six weeks of culture, size variation after six weeks was large due to the high density of shrimp. The experiment showed that old acid sulphate soil-affected ponds, in which the bottom soil has not been excavated any further, can be used for production of juvenile shrimp in hapas. Rearing over three weeks is recommended to obtain high survival and reduce size variation.